Aptamers in Virology: Recent Advances and Challenges - Binning, Jennifer M.; Leung, Daisy W.; Amarasinghe, Gaya (Frontiers in Microbiology, 2012)
Aptamers generated from randomized libraries of nucleic acids have found utility in a wide variety of fields and in the clinic. Aptamers can be used to target both intracellular and extracellular components, including small molecules, proteins, cells, and viruses. With recent technological developments in stringent selection and rapid isolation strategies, it is likely that aptamers will continue to make an impact as useful tools and reagents. Although many recently developed aptamers are intended for use as therapeutic and diagnostic agents, use of aptamers for basic research, including target validation remains an active area with high potential to impact our understanding of molecular mechanisms and for drug discovery. In this brief review, we will discuss recent aptamer discoveries, their potential role in structural virology as well as challenges and future prospects.